2020
DOI: 10.1039/d0bm01249a
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-based, injectable microcarriers for controlled delivery of interleukin-13 to the brain

Abstract: The anti-inflammatory cytokine IL-13 can be loaded and released from heparin-based cryogel biomaterials for sustained delivery to the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Macro-scale protein drug delivery systems are used to control the delivery of drugs to specific tissues. Careful material selection is often required for establishing an effective polymer drug delivery system for a particular protein, achieving the desired protein release profile, and maintaining bioactivity [ 56 ]. In drug-loaded cryogels, because the porous structure triggers the burst release of the drug, the use of a nanocarrier to overcome this situation could be a potential candidate for both controlling the drug release rate and enhancing the cryogels [ 57 ].…”
Section: Injectable Cryogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Macro-scale protein drug delivery systems are used to control the delivery of drugs to specific tissues. Careful material selection is often required for establishing an effective polymer drug delivery system for a particular protein, achieving the desired protein release profile, and maintaining bioactivity [ 56 ]. In drug-loaded cryogels, because the porous structure triggers the burst release of the drug, the use of a nanocarrier to overcome this situation could be a potential candidate for both controlling the drug release rate and enhancing the cryogels [ 57 ].…”
Section: Injectable Cryogelsmentioning
confidence: 99%
“…Here, microscale cryogels (microcarriers) containing heparin and PEG were employed, and characterization processes were carried out. Immunomodulatory activity of IL-13 loaded microcarriers was evaluated in vitro on bone marrow-derived macrophages and in vivo in mouse brain, and it was emphasized that a slow and sustained IL-13 release was achieved with microcryogels for at least seven days [ 56 ].…”
Section: Injectable Cryogels In Biomedicine Applicationsmentioning
confidence: 99%
“…An overview of different cryogels prepared on the basis of HA, CS, and HE and their derivatives, respectively, is provided in Tables 1 and 2. Carrier for pancreative islets [41] Cancer immunotherapy [42] Cytokine release to the brain [43] stem cell culture; RGD-modification-mediated cell adhesion Neural cell cultivation [44,45]…”
Section: Overview Of Gag-based Cryogelsmentioning
confidence: 99%
“…Due to the known disadvantages of physical crosslinking, such as poor mechanical stability, difficult adjustability of the pore size, and the often-rapid degradation behavior, many researchers use chemical methods of crosslinking [ 53 , 54 ]. Several common low-molecular crosslinking agents such as diepoxides [ 15 ], glutar dialdehyde [ 23 , 37 , 49 ], divinylsulfone [ 17 ], or water-soluble carbodiimides (e.g., 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide) [ 18 , 19 , 20 , 35 , 36 ], mostly in the presence of N-Hydroxysulfosuccinimide (Sulfo-NHS) [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], have also been used for the preparation of GAG-based cryogels. Besides those low-molecular-weight crosslinkers, also oligomeric bifunctional crosslinkers, for example a polycaprolactone-based diisocyanate (PCl-di-NCO) and poly(ethylene glycol)bis-maleimide (PEG-bis(maleimide)), have been used to initiate crosslinking by urethane formation [ 23 ] and a Diels−Alder click-crosslinked reaction with a furan-modified HA [ 33 , 34 ], respectively.…”
Section: Preparation Of Gag-based Cryogelsmentioning
confidence: 99%
“…Although numerous studies have shown that intracerebral injection of microencapsulated growth factors including GDNF [33][34][35][36][37][38][39] and vascular endothelial growth factor (VEGF) [34,35,40] can improve parkinsonism in both rodent [34][35][36][37][38][39][40][41][42] and primate [33] models of PD, the main limitation of this approach is that the growth factor release in the brain is rapid and not sustained, a major issue if biomaterial-aided growth factor therapy is to provide meaningful benefit in the decades-long pathogenesis of PD in patients. One potential solution to this could be the use of highly charged microscale depot systems that provide strong electrostatic attraction between the therapeutic protein(s) and the microcarrier [43]. Not only does this result in slower release of the therapeutic protein, but it also has the potential to be refillable or reloadable, although this too is limited as each refill would require intracerebral injection of the growth factor.…”
Section: Routementioning
confidence: 99%